2014
DOI: 10.1002/mame.201300449
|View full text |Cite
|
Sign up to set email alerts
|

Macroporous Nanocomposite Materials Prepared by Solvent Evaporation from Pickering Emulsion Templates

Abstract: Hydroxyapatite (HAp)/poly(L‐lactic acid) (PLLA) interconnected macroporous materials are facilely and effectively fabricated by templating water‐in‐dichloromethane with PLLA (W/O) Pickering emulsions. The HAp nanoparticles modified with PLLA (g‐HAp nanoparticles) are used as effective particulate emulsifiers to produce stable W/O Pickering emulsions. Evaporation of the W/O Pickering emulsions directly leads to interconnected porous nanocomposite materials in absence of any chemical reactions. This simple and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In this work, PLLA molecules with carboxyl end groups were used as the biodegradable and biocompatible modifiers to modify the HAp nanoparticles. PLLA molecules were grafted onto HAp surface by forming calcium carboxylate bonds between carboxyl end groups of PLLA and calcium ions on the HAp surfaces. SEM and TEM studies of the dried g-HAp nanoparticles (Figure a and Supporting Information (SI) Figure S1) indicated that the g-HAp nanoparticles were irregular shape with broad diameter distribution. Dynamic light scattering study of dilute CH 2 Cl 2 dispersion of g-HAp nanoparticles (SI Figure S2a) showed that the mean diameter of g-HAp nanoparticles was about 580 nm.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, PLLA molecules with carboxyl end groups were used as the biodegradable and biocompatible modifiers to modify the HAp nanoparticles. PLLA molecules were grafted onto HAp surface by forming calcium carboxylate bonds between carboxyl end groups of PLLA and calcium ions on the HAp surfaces. SEM and TEM studies of the dried g-HAp nanoparticles (Figure a and Supporting Information (SI) Figure S1) indicated that the g-HAp nanoparticles were irregular shape with broad diameter distribution. Dynamic light scattering study of dilute CH 2 Cl 2 dispersion of g-HAp nanoparticles (SI Figure S2a) showed that the mean diameter of g-HAp nanoparticles was about 580 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Dichloromethane (CH 2 Cl 2 ) was purchased from Guangzhou Chemical Factory (Guangzhou, China). The preparation of HAp nanoparticles and their surface hydrophobicity modification by PLLA containing carboxyl end groups (g-HAp) have been described in our previous work [37]. The particle diameters of g-HAp nanoparticles were in the range from 30 to 70 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The HAp/PLLA NC scaffolds were fabricated by solvent evaporation from templating water-in-oil (W/O) Pickering emulsions according to the procedures reported in our previous study [37]. Firstly, the calculated amount of g-HAp nanoparticles was dispersed in a 4 w/v% CH 2 Cl 2 solution of PLLA (total, 5 mL) by ultrasonication at 0 • C for 10 min.…”
Section: Fabrication Of Hap/plla Nc Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…E. coli was picked on the antibacterial effect, and also biocompatibility was verified by the cytotoxicity test of the epithelial cells. Furthermore, we prepared pH-sensitive NCs via Pickering encapsulation technology [29][30][31][32]. These NCs release their cargo above pH 5 when the humidity is high, conditions in which most bacteria, including Escherichia coli and fungi, are active.…”
Section: Introductionmentioning
confidence: 99%